Novel cytokinin derivatives do not show negative effects on root growth and proliferation in submicromolar range - Podlešáková, Kateřina; Zalabák, David; Cudejková, Mária; Plíhal, Ondřej; Szüčová, Lucie; Doležal, Karel; Spíchal, Lukáš; Strnad, Miroslav; Galuszka, Petr (PloS one, 2012)
BACKGROUND: When applied to a nutrition solution or agar media, the non-substituted aromatic cytokinins caused thickening and shortening of the primary root, had an inhibitory effect on lateral root branching, and even showed some negative effects on development of the aerial part at as low as a 10 nanomolar concentration. Novel analogues of aromatic cytokinins ranking among topolins substituted on N9-atom of adenine by tetrahydropyranyl or 4-chlorobutyl group have been prepared and tested in standardized cytokinin bioassays [1]. Those showing comparable activities with N(6)-benzylaminopurine were further tested in planta. METHODOLOGY/PRINCIPAL FINDINGS: The main aim of the study was to explain molecular mechanism of function of novel cytokinin derivatives on plant development. Precise quantification of cytokinin content and profiling of genes involved in cytokinin metabolism and perception in treated plants revealed several aspects of different action of m-methoxytopolin base and its substituted derivative on plant development. In contrast to standard cytokinins, N9- tetrahydropyranyl derivative of m-topolin and its methoxy-counterpart showed the negative effects on root development only at three orders of magnitude higher concentrations. Moreover, the methoxy-derivative demonstrates a positive effect on lateral root branching and leaf emerging in a nanomolar range of concentrations, in comparison with untreated plants. CONCLUSIONS/SIGNIFICANCE: Tetrahydropyranyl substitution at N9-position of cytokinin purine ring significantly enhances acropetal transport of a given cytokinins. Together with the methoxy-substitution, impedes accumulation of non-active cytokinin glucoside forms in roots, allows gradual release of the active base, and has a significant effect on the distribution and amount of endogenous isoprenoid cytokinins in different plant tissues. The utilization of novel aromatic cytokinin derivatives can distinctively improve expected hormonal effects in plant propagation techniques in the future.
Keywords: Arabidopsis; oxidoreduktasy; semenáček; Plant Leaves; kukuřice setá; Cell Proliferation; cytokininy; biomasa; Xylem; xylém; Plant Growth Regulators; proliferace buněk; Gene Expression Regulation, Plant; listy rostlin; Plant Roots; regulátory růstu rostlin; Biomass; Enzyme Activation; stanovení celkové genové exprese; kořeny rostlin; Zea mays; regulace genové exprese u rostlin; Gene Expression Profiling; Cytokinins; Oxidoreductases; aktivace enzymů; Seedlings